2011
DOI: 10.1055/s-0031-1280359
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Efficacy of a Quantified Extract ofNauclea pobeguiniiStem Bark in Human Adult Volunteers with Diagnosed Uncomplicated Falciparum Malaria. Part 1: A Clinical Phase IIA Trial

Abstract: The aim of this phase IIA clinical trial was to assess the efficacy of an 80 % ethanolic quantified extract (containing 5.6 % strictosamide as the putative active constituent) from Nauclea pobeguinii stem bark denoted as PR 259 CT1 in a small group of adult patients diagnosed with uncomplicated falciparum malaria. Results obtained from a phase I clinical trial on healthy male volunteers indicated that the oral administration during meals of two 500 mg capsules three times daily (each eight hours) during seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The Phase IIA study was an open cohort study on 11 adult patients suffering from proven Plasmodium falciparum malaria using a therapeutic dose which was calculated from animal doses. This clinical trial was carried out according to the WHO 2003 14-day test, and the results revealed that 10 out of 11 patients were completely cleared of parasitaemia and fever at days 3, 7, and 14, and that the herbal medicinal product was well tolerated with only mild and self-resolving adverse effects including asthenia and headache, confirming the findings of the Phase I clinical trial [9]. Taking into account these promising results, it was decided to assess the putative efficacy and the safety of the oral treatment of PR 259 CT1 on a larger number of patients suffering from uncomplicated Plasmodium falciparum malaria in comparison with an artesunate-amodiaquine (AS-AQ) combination according to the WHO 2003 protocol criteria which could then ultimately lead to a Phase III clinical trial study.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The Phase IIA study was an open cohort study on 11 adult patients suffering from proven Plasmodium falciparum malaria using a therapeutic dose which was calculated from animal doses. This clinical trial was carried out according to the WHO 2003 14-day test, and the results revealed that 10 out of 11 patients were completely cleared of parasitaemia and fever at days 3, 7, and 14, and that the herbal medicinal product was well tolerated with only mild and self-resolving adverse effects including asthenia and headache, confirming the findings of the Phase I clinical trial [9]. Taking into account these promising results, it was decided to assess the putative efficacy and the safety of the oral treatment of PR 259 CT1 on a larger number of patients suffering from uncomplicated Plasmodium falciparum malaria in comparison with an artesunate-amodiaquine (AS-AQ) combination according to the WHO 2003 protocol criteria which could then ultimately lead to a Phase III clinical trial study.…”
supporting
confidence: 61%
“…Follow-up of patients was carried out as reported for the Phase I and IIA studies [8,9] and also included electrocardiogram (ECG) examinations. The 12-derivative standard ECG was recorded using a Cardiofax ECG-6851K electrocardiograph (Nihon Kohden) and analysed manually.…”
Section: Follow-up Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also non-toxic: no acute toxicity was observed in mice after a single 2 g/kg oral dose, nor after 4 weekly doses (Mesia et al, 2010). Furthermore it is safe and effective against uncomplicated malaria in humans (Mesia et al, 2011;Mesia et al, 2012a;Mesia et al, 2012b). One of the active compounds is thought to be strictosamide.…”
Section: Familymentioning
confidence: 99%
“…There are other fever-reducing folk remedies that could yield a next-generation antimalarial. For example, the bark of the plant Nauclea pobeguinii , from the Democratic Republic of Congo, can substantially reduce parasitemia in mice infected with rodent malaria 97 and has shown efficacy in man in phase IIb clinical trials 98 . It is interesting to note that the chemical structure of a possible active ingredient, strictosamide, is similar to that of the spiroindolones 99 .…”
Section: Natural Products New Formulations and Combination Therapiesmentioning
confidence: 99%